Her day in court [videorecording (VHS)] : women and justice in Washington State - Starbuck, Susan (American Motion Pictures, 1988)
Currently, 11% of the judges in Washington State are women. This program interviews some of the first women lawyers and judges in the state, discussing the struggle and rise of women in the judiciary.